Granulometric assessment of sediment accumulation for desilting the Toukomtoré agricultural water reservoir in Burkina Faso - Ilboudo , Adama; Yameogo , P. Louis; Kabore , Joseph Nomwindé; Guébré , Daouda; Ouédraogo , Harouna; Hien, Edmond (Brawijaya University, 2026)
Sedimentation of small reservoirs is a critical factor in the degradation of land and water resources in the Sudano-Sahelian zone. Such infrastructure underpins agricultural resilience and rural livelihoods. This study used an integrated granulometric, morphometric, and spatial analysis to evaluate sediment accumulation in the Toukomtoré reservoir in Koubri, central Burkina Faso, and to inform degraded land management strategies. Ten sediment cores (maximum depth: 1.50 m) were collected along transects spanning the upstream-downstream and center-periphery axes. Thirty samples were analyzed for particle size distribution, and key parameters such as the Hazen uniformity coefficient (Cu) and the classification coefficient (Cc) were computed. Spatial interpolation was performed using QGIS, and statistical analyses were performed using R 4.4.3. The results indicate a mean sediment deposition of 90 cm, peaking at 119 cm in the upstream and central zones, which are dominated by sand (64%-80%). Subsurface layers are predominantly sandy (80%), while surface horizons show enrichment of silt and clay, indicating recent deposition. The bulk density ranged from 1.55 to 1.63 g/cm³. Critical degradation drivers include a steep watershed slope of 10.5 m/km, sparse vegetation, unsustainable tillage practices, and the absence of soil conservation structures. This sedimentation process severely reduces reservoir storage capacity and accelerates land degradation. To mitigate erosion and prolong infrastructure lifespan, this study recommends integrated watershed interventions, including vegetative buffers, check dams, and agroforestry. This study provides policymakers who manage small reservoirs in semi-arid, degraded landscapes with actionable data.